Knowledge, practices, and perceived barriers regarding cancer pain management among physicians and nurses in Korea: a nationwide multicenter survey. - Hyun Jung Jho (Public Library of Science (PLoS), 2014)
Purpose Medical professionals' practices and knowledge regarding cancer pain management have often been cited as inadequate. This study aimed to evaluate knowledge, practices and perceived barriers regarding cancer pain management among physicians and nurses in Korea. Methods A nationwide questionnaire survey was administered to physicians and nurses involved in the care of cancer patients. Questionnaire items covered pain assessment and documentation practices, knowledge regarding cancer pain management, the perceived barriers to cancer pain control, and processes perceived as the major causes of delay in opioid administration. Results A total of 333 questionnaires (149 physicians and 284 nurses) were analyzed. Nurses performed pain assessment and documentation more regularly than physicians did. Although physicians had better knowledge of pain management than did nurses, both groups lacked knowledge regarding the side effects and pharmacology of opioids. Physicians working in the palliative care ward and nurses who had received pain management education obtained higher scores on knowledge. Physicians perceived patients' reluctance to take opioids as a barrier to pain control, more so than did nurses, while nurses perceived patients' tendency to under-report of pain as a barrier, more so than did physicians. Physicians and nurses held different perceptions regarding major cause of delay during opioid administration. Conclusions There were differences between physicians and nurses in knowledge and practices for cancer pain management. An effective educational strategy for cancer pain management is needed in order to improve medical professionals' knowledge and clinical practices.